Pengujian Black Box pada Aplikasi Inventaris Berbasis Web Menggunakan Metode Equivalents Partitions - Mayrina Setiadi; Ari Sulistyo Wibowo; Puji Raja Bagus Kausar; Aries Saifudin (CV. Multi Kreasi Media, 2023)
Website Based Inventory Applicatin at Akmal Store is an application that assists Akmal Store in providing website based product stock record storage media. With the Akmal Store Inventory application, hoped that it can assist Akmal Stores in providing storage media for product stock records using a database. As well as helping Akmal Stores in recording product stocks to be easier, accurate and modern so, when reporting the stock of products it will be even better in the future. Before using the web-based Inventory application at the Akmal Store, it is necessary to test the application to find out errors in the function of each menu on the web-based Inventory application at the Akmal Store. Testing on the web-based Inventory application at Toko Akmal is carried out on the menu function using the black box method based on Equivalents Partitions. Black box testing is quality testing that focuses on software functionality. The purpose of black box testing is to find function errors, interface errors, data structure errors, performance errors, initialization errors and termination errors. Equivalents Partitions is a test based on data entry in the form contained in the web-based Inventory application at the Akmal Store. Each input field will be tested and grouped based on its function. After completing nine test cases, it can be concluded that in the web-based Inventory application at the Akmal Store, no errors were found in the function of each menu.